Tourism economics and policy - Dwyer, Larry; Forsyth, P. (Peter); Dwyer, Wayne (Bristol, UK : Channel View Publications, 2010)
'Tourism Economics and Policy combines a comprehensive treatment of economic concepts and applications in tourism contexts. The topics covered are those that most occupy the attention of tourism economists in research and policy areas internationally. Content includes tourism demand and forecasting; tourism supply and pricing; measuring tourism's economic contribution using tourism satellite accounts; measuring the impacts and benefits of changes in tourism demand, contrasting Input-output and computable general equilibrium modelling; cost benefit analysis; economic evaluation of special events; tourism investment and infrastructure; tourism taxation; aviation and tourism issues, tourism and the environment (including climate change) and destination competitiveness. The text provides an excellent basis for students to appreciate the relevance of economic analysis to the solution of real life tourism issues as well as its importance for decision making by both destination managers and tourism operators.'--pub. desc.
Includes bibliographical references and index.
Keywords: Tourism -- Forecasting; Tourism -- Management; Tourism -- Government policy